eCM 2014
DOI: 10.22203/ecm.v027a08
|View full text |Cite
|
Sign up to set email alerts
|

Spatial control of bone formation using a porous polymer scaffold co-delivering anabolic rhBMP-2 and anti-resorptive agents

Abstract: Current clinical delivery of recombinant human bone morphogenetic proteins (rhBMPs) utilises freeze-dried collagen. Despite effective new bone generation, rhBMP via collagen can be limited by significant complications due to inflammation and uncontrolled bone formation. This study aimed to produce an alternative rhBMP local delivery system to permit more controllable and superior rhBMP-induced bone formation. Cylindrical porous poly(lactic-co-glycolic acid) (PLGA) scaffolds were manufactured by thermally-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Although bisphosphonates have primarily been given to increase or maintain bone mineral content in patients with low bone density, in animal models, systemic bisphosphonates can also be used to block the BMP mediated bone resorption and pharmacologically balance the anabolic and anti-catabolic effects of the two drugs 16 21 . Further, there is room for improvements regarding the delivery of the protein and BMP’s have been delivered using carboxymethyl cellulose (CMC) or bovine collagen particles 16 as carriers, or by impregnation of collagen sponges 12 39 41 46 and other polymers 47 . These carriers have limitations, like the impregnation time that can lead to varying clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although bisphosphonates have primarily been given to increase or maintain bone mineral content in patients with low bone density, in animal models, systemic bisphosphonates can also be used to block the BMP mediated bone resorption and pharmacologically balance the anabolic and anti-catabolic effects of the two drugs 16 21 . Further, there is room for improvements regarding the delivery of the protein and BMP’s have been delivered using carboxymethyl cellulose (CMC) or bovine collagen particles 16 as carriers, or by impregnation of collagen sponges 12 39 41 46 and other polymers 47 . These carriers have limitations, like the impregnation time that can lead to varying clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of osteoclast activity using anti‐catabolic drugs such as bisphosphonates can further increase total bone. In such studies, intra‐muscular rhBMP‐2 implantation models translated to more sophisticated gap healing models . While it is currently unclear whether APC treatment alone would translate to improvements in fracture repair, it is hypothesized that APC could augment rhBMP‐2 induced bone formation in other orthopedic models.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical surface modification, such as silanes treatments, are usually exploited in order to improve their surface reactivity and biocompatibility ( Puppi et al, 2010 ; Jaidev and Chatterjee, 2019 ), as well as surface functionalization with bioactive molecules, such as rhBMP2, BMP7 or RGD peptides, aiming to significantly improve cells adhesion, proliferation and new bone formation in vitro and in vivo ( Rahman et al, 2014 ; Kim et al, 2015 ; Shin et al, 2015 ). In particular, it has been recently shown that porous PLGA scaffolds loaded with both rhBMP2 and BTTs, e.g., zoledronic acid and IkappaB kinase (IKK)-inhibitors promoted both bone regeneration and antiresorptive activity in order to stimulate healing of critical bone defects in rats ( Yu et al, 2014 ). The promising results of this work open the possibility to design new medicated scaffolds with both pro-regenerative molecules and antineoplastic agents to better treat BM patients.…”
Section: Biomaterials For Bone Tissue Applicationsmentioning
confidence: 99%